Radiation induced DNA DSBs: Contribution from stalled replication forks? - Harper, J; Anderson, J; O'Neill, P (2010)
When cells are exposed to radiation serious lesions are introduced into the DNA including double strand breaks (DSBs), single strand breaks (SSBs), base modifications and clustered damage sites (a specific feature of ionizing radiation induced DNA damage). Radiation induced DNA damage has the potential to initiate events that can lead ultimately to mutations and the onset of cancer and therefore understanding the cellular responses to DNA lesions is of particular importance. Using gammaH2AX as a marker for DSB formation and RAD51 as a marker of homologous recombination (HR) which is recruited in the processing of frank DSBs or DSBs arising from stalled replication forks, we have investigated the contribution of SSBs and non-DSB DNA damage to the induction of DSBs in mammalian cells by ionizing radiation during the cell cycle. V79-4 cells and human HF19 fibroblast cells have been either irradiated with 0-20Gy of gamma radiation or, for comparison, treated with a low concentration of hydrogen peroxide, which is known to induce SSBs but not DSBs. Inhibition of the repair of oxidative DNA lesions by poly(ADP ribose) polymerase (PARP) inhibitor leads to an increase in radiation induced gammaH2AX and RAD51 foci which we propose is due to these lesions colliding with replication forks forming replication induced DSBs. It was confirmed that DSBs are not induced in G(1) phase cells by treatment with hydrogen peroxide but treatment does lead to DSB induction, specifically in S phase cells. We therefore suggest that radiation induced SSBs and non-DSB DNA damage contribute to the formation of replication induced DSBs, detected as RAD51 foci.